Pengaruh permainan bocce pada keterampilan gerakan manipulatif anak-anak penyandang cacat intelektual - Bulu Baan, Addriana; Sardiman, Sardiman; Purwanto, Didik (Universitas Nusantara PGRI Kediri, 2023)
This study aimed to determine the Effect of Bocce Games on the Manipulative Movements of Mentally Impaired Children at SLB Muhammadiyah ABC Palu. This research is a type of experimental design research using a pretest-posttest one-group design. The research sample was 10 students selected by purposive sampling technique. The data analysis techniques used are Descriptive Analysis, Normality Test, and SPSS. This study used the Throw Fun Target Test instrument to modify the Bocce game with a model of throwing the ball at the target/target with coordination movements. The results showed that the results of statistical tests with t-test techniques showed a sig value of 0.000 so that which was smaller than the significant level used (p < 0.05), furthermore, the results of the pretest and posttest results of the bocce game showed a difference in the mean value of pretest 1.8000 and posttest 3.6000. This means that from this study, there is an influence of bocce games to provide significant results on the manipulative movement of children with intellectual disabilities SLB Muhammadiyah ABC Palu.